Acid stimulated alkaline secretion in the rabbit duodenum is passive and correlates with mucosal damage. Issue 3 (March 1988) - Vattay, P; Feil, W; Klimesch, S; Wenzl, E; Starlinger, M; Schiessel, R
Abstract : Low luminal acid concentrations stimulate alkaline secretion (AS) by the duodenal mucosa. We investigated acid stimulated alkaline secretion by proximal rabbit duodenal mucosa in an Ussing-chamber under different luminal acid concentrations and its relation to mucosal damage. Luminal alkalinisation and potential difference (PD) were measured and mucosal damage was investigated histologically. Luminal acid caused an increase of alkaline secretion over baseline (0.95 +/- 0.19 mu Eq/cm2/10 min; n = 55): 0.1 mmol: 7%, 1 mmol/l: 17%, 5 mmol/l: 22%, 10 mmol/l: 33%, 20 mmol/l: 34%, 50 mmol: 39%, 100 mmol/l: 27%. At acid concentrations of 10 mmol/l and above the PD fell from 2.0 +/- 1.0 mV to zero. Histology showed [H+]-dependent mucosal damage ranging from villus tip lesions to deep mucosal injury. Stimulation of alkaline secretion was not specific for acid. Ethanol (14%) stimulated alkaline secretion by 26%, and 28% ethanol by 40% over baseline. Ouabain and/or anoxia sensitive (active) alkaline secretion constituted 80% and 100% respectively of basal alkaline secretion. After exposure to various luminal acid concentrations passive diffusion (sensitive only to removal of nutrient HCO3-) was solely responsible for the rise in alkaline secretion. Only after 14% ethanol a small rise in ouabain and/or anoxia sensitive HCO3- transport was observed. Under the conditions of this study stimulation of duodenal alkaline secretion is not specific for luminal acid, but occurs also with luminal ethanol; both agents stimulate alkaline secretion depending on their concentration. In this model passive diffusion of HCO3- associated with increasing mucosal damage is the major component of the rise in alkaline secretion.